THE INFLUENCE OF PERSONALITY, ENTREPRENEURIAL KNOWLEDGE, AND FAMILY ENVIRONMENT ON ENTREPRENEURIAL INTERESTS OF STUDENTS OF CLASS XII SMKN 1 KEBUMEN CENTRAL JAVA: PENGARUH KEPRIBADIAN, PENGETAHUAN KEWIRAUSAHAAN, DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XII SMKN 1 KEBUMEN JAWA TENGAH - Sari Wahyu Utami; Sri Zulaihati; Ati Sumiati (Yayasan Education and Social Center, 2022)
This study aims to determine whether personality, entrepreneurial knowledge, and family environment affect the interest in entrepreneurship in class XII students of SMKN 1 Kebumen, Central Java. The research method used is a survey method with a quantitative approach. The affordable population in this study were all class XII of SMKN 1 Kebumen majoring in accounting, totalling 143 students. The sample used was 105 students using the proportional random sampling technique. The instrument used to obtain data on the variables of personality (X1), family environment (X2), and interest in entrepreneurship (Y) used a questionnaire with a Likert scale that had been tested for validity and reliability. Then for the entrepreneurial knowledge variable (X2), secondary data is used in report cards for entrepreneurship subjects. The data collection results were then analyzed through multiple linear regression and hypothesis testing with the help of SPSS version 26. The results showed that personality, entrepreneurial knowledge, and family environment had a positive and significant impact on entrepreneurial interest, contributing 35.1%.